Changing Educational Landscapes: Student Learning, Artificial Intelligence and the Attention Economy - Webster, Ray; Andre, John; Le, Kien (VNU Journal of Science: Education Research; Vol 42 No 1, 2026)
Artificial Intelligence (AI) and the Attention Economy are both having profound effects on the way we live and learn. It is their interactions that are producing major changes in the way that new generations are developing mentally, emotionally and educationally. This paper is concerned with enabling and developing student learning and coping mechanisms against the background of the AI-driven Attention Economy. Several current and emerging problems, rooted in the interaction between AI and the Attention Economy, which affect student learning and personal development, are considered. These include the areas of attentional capacity, memory processes and social cognition. The important role of self-awareness for student development and autonomy in this changing learning process is considered, especially in the light of the recent update of the framework for 21 st Century Learning by the Center for Curriculum Redesign. The development of artificial intelligence and the possibility of providing AI-based Individual Learning Assistants which would work alongside the students, rather than acting as a feeder of personal data to the major technology companies is also discussed. Two separate themes emerge which are the potential uses of AI to improve education and the much broader societal educational, anxiety and mental health issues outlined by Jonathan Haidt, and most impacting those born after 1997 (Gen Z and Gen Alpha). The major issues of each theme are presented and discussed before potential solutions are briefly outlined. The latter includes consideration of the extensive implementation of a ban on smart phone use in Australia’s public schools from the start of 2024.